2009
DOI: 10.1080/09397140.2009.10638351
|View full text |Cite
|
Sign up to set email alerts
|

At the interface of historical and present-day ecology: ground beetles in woodlands and open habitats in Upper Galilee (Israel)

Abstract: Mediterranean landscapes have been used by humans for thousands of years, particularly some areas of the East Mediterranean, e.g. in Israel. This land use has had profound effects on the dynamics of the woodlands in time and space, with the result that woodland regeneration has only been possible during periods of low human population density and hence low levels of grazing. The aim of this paper is therefore to find out how woodland species have been able to cope with the rapidly changing habitats. For this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…This alarming development is in contrast with the overall importance of the region as a biodiversity hotspot (Yom-Tov and Tchernov, 1988). Open spaces are important habitats for Israels biodiversity (Filser and Prasse, 2008;Timm et al, 2009). In order to find effective solutions to conserve a maximum of biodiversity in the region, more research and a management strategy for the remaining open space is urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…This alarming development is in contrast with the overall importance of the region as a biodiversity hotspot (Yom-Tov and Tchernov, 1988). Open spaces are important habitats for Israels biodiversity (Filser and Prasse, 2008;Timm et al, 2009). In order to find effective solutions to conserve a maximum of biodiversity in the region, more research and a management strategy for the remaining open space is urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…In recent woodlands (less than 50 years old) at an altitude of about 700 m a.s.l., dominated by about 5 m high Quercus calliprinos Webb. trees, 21 species belonging to 12 genera were found (Timm et al 2009). Thirty-two carabid species were captured in juniper maquis formations in five sampling sites in Greece (Kaltsas et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This study is based on the examination of specimens (i) observed and/or collected during field trips of the authors in Israel, Jordan andEgypt (between 2004 and, (ii) collected in context of ecological surveys (e.g., Timm et al 2009), and/or (iii) stored in entomological collections (incl. historical collections).…”
Section: Methodsmentioning
confidence: 99%
“…Probably an autumn and winter breeder. Timm et al (2009) caught three individuals in a survey with pitfall traps open continuously for an entire year and these exclusively in November and December. A newly hatched beetle at the end of March on the Golan Heights.…”
Section: Olisthopus Fuscatus Dejean 1828mentioning
confidence: 99%